Complications in using automated methods to increase clinical trial accrual. (9th August 2010) - Fefilatyev, Sergiy; Chen, Li; Ivanovskiy, Tim V.; Hall, Lawrence O.; Goldgof, Dmitry; Greenstien, Halina; Garrett, Christopher
This paper describes the issues involved in improving accruals for clinical trials using a web-based system. We installed a custom web-based expert system at the H. Lee Moffitt Cancer Center and Research Institute to help physicians screen patients for phase II clinical trials. The system allows physicians to screen a patient for multiple trials simultaneously. Experiments have shown that adaptation of the system into a clinical environment and the success of the system are related to the amount of time physicians are willing to spend entering data. We also found significant regulatory issues (HIPAA) that make implementation challenging.